Anti-inflammatory effect of simvastatin in an experimental model of spinal cord trauma: involvement of PPAR-α - Esposito Emanuela; Rinaldi Barbara; Mazzon Emanuela; Donniacuo Maria; Impellizzeri Daniela; Paterniti Irene; Capuano Annalisa; Bramanti Placido; Cuzzocrea Salvatore (Journal of Neuroinflammation, 2012)
Abstract Background Statins such as simvastatin are inhibitors of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase used in the prevention of cardiovascular disease. In addition to their cholesterol-lowering activities, statins exert pleiotropic anti-inflammatory effects, which might contribute to their beneficial effects on lipid-unrelated inflammatory diseases. Recently it has been demonstrated that the peroxisome proliferator-activated receptor (PPAR)-α mediates anti-inflammatory effects of simvastatin in vivo models of acute inflammation. Moreover, previous results suggest that PPAR-α plays a role in control of secondary inflammatory process associated with spinal cord injury (SCI). Methods With the aim to characterize the role of PPAR-α in simvastatin activity, we tested the efficacy of simvastatin (10 mg/kg dissolved in saline i.p. 1 h and 6 h after the trauma) in an experimental model of SCI induced in mice by extradural compression of the spinal cord (T6-T7 level) using an aneurysm clip with a closing force of 24 g via a four-level T5-T8 laminectomy, and comparing mice lacking PPAR-α (PPAR-α KO) with wild type (WT) mice. In order to elucidate whether the effects of simvastatin are due to activation of the PPAR-α, we also investigated the effect of a PPAR-α antagonist, GW6471 (1 mg/kg administered i.p. 30 min prior treatment with simvastatin) on the protective effects of on simvastatin. Results Results indicate that simvastatin activity is weakened in PPAR-α KO mice, as compared to WT controls. In particular, simvastatin was less effective in PPAR-α KO, compared to WT mice, as evaluated by inhibition of the degree of spinal cord inflammation, neutrophil infiltration, nitrotyrosine formation, pro-inflammmatory cytokine expression, nuclear factor (NF)-κB activation, inducible nitric-oxide synthase (iNOS) expression, and apoptosis. In addition we demonstrated that GW6471 significantly antagonized the effect of the statin and thus abolished the protective effect. Conclusions This study indicates that PPAR-α can contribute to the anti-inflammatory activity of simvastatin in SCI.